2020
DOI: 10.1186/s13195-020-00651-0
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in EEG power, sleep cycles and behaviour in a tau model of neurodegeneration

Abstract: Background: Disturbed sleep is associated with cognitive decline in neurodegenerative diseases such as Alzheimer's disease (AD) and frontotemporal dementia (FTD). The progressive sequence of how neurodegeneration affects aspects of sleep architecture in conjunction with behavioural changes is not well understood. Methods: We investigated changes in sleep architecture, spectral power and circadian rhythmicity in the tet-off rTg4510 mouse overexpressing human P301L tau within the same subjects over time. Doxycyc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 62 publications
(92 reference statements)
1
37
0
Order By: Relevance
“…Reduced REMS duration is a predictor of incident dementia and one of the most prominent changes in the sleep EEG in mild cognitive impairment ( Hita-Yañez et al, 2012 ; Pase et al, 2017 ). A recent longitudinal study in rTg4510 mice showed that REMS continuity was reduced with a decreased episode length in the dark and light periods from respectively 24 and 32 weeks of age, and a reduced number of episodes in the dark period from 40 weeks of age ( Holton et al, 2020 ). A decrease in NREMS duration was also observed from 28 weeks old in the dark phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced REMS duration is a predictor of incident dementia and one of the most prominent changes in the sleep EEG in mild cognitive impairment ( Hita-Yañez et al, 2012 ; Pase et al, 2017 ). A recent longitudinal study in rTg4510 mice showed that REMS continuity was reduced with a decreased episode length in the dark and light periods from respectively 24 and 32 weeks of age, and a reduced number of episodes in the dark period from 40 weeks of age ( Holton et al, 2020 ). A decrease in NREMS duration was also observed from 28 weeks old in the dark phase.…”
Section: Discussionmentioning
confidence: 99%
“…Mice underwent in-house surgery at 3-month-old (weight: 29.3 ± 0.4 g). Subjects were anesthetised (2% isoflurane in 100% oxygen, 0.1mg/kg medetomidine HCl subcutaneous (SC) injection) and surgically prepared for chronic electroencephalogram (EEG) and electromyogram (EMG) recordings as previously described (Holton et al, 2020). The cranial implant consisted of five stainless steel screws for EEG recording (frontal electrode: 2-mm anterior to bregma and 2-mm left of the sagittal suture line; occipital electrode: 3-mm caudal from bregma and 3-mm right of the sagittal suture line; two stabilising screws opposite to the frontal and occipital electrodes; one ground electrode over the cerebellum).…”
Section: Surgical Procedures For Eeg/emg Sleep Studymentioning
confidence: 99%
“…The sleep-wake cycle has been examined across different pathological stages in various mouse models, including 3xTg-AD [233,234], APP/PS1 [234,235], Tg2576 [234,236], P301S Tau [237], rTG4510 [238], PLB1 Triple [239], and PLB2tau [240] models (Table 3). Slow (<1 Hz) oscillations have been analysed together with delta oscillations (1-4 Hz), which can be used to determine NREM sleep.…”
Section: Slow Oscillations and Ad In Mouse Modelsmentioning
confidence: 99%
“…Slow (<1 Hz) oscillations have been analysed together with delta oscillations (1-4 Hz), which can be used to determine NREM sleep. In several AD mouse models, NREM sleep is reduced and fragmented [233,234,237,238], which implies that changes also occur in the patterns of slow oscillations. It has been suggested that the reduction in GABAergic tone impairs longrange synchronous firing in an amyloid mouse model [92].…”
Section: Slow Oscillations and Ad In Mouse Modelsmentioning
confidence: 99%
“…The rTg(tau301L 4R0N) 4510 mouse model (SantaCruz et al, 2005) expresses high levels of human tau (up to 13-fold of its normal murine level) with a mutation that has been linked to familial frontotemporal dementia, the second most prevalent neurodegenerative disease (Clark et al, 1998;Dumanchin et al, 1998;Hutton et al, 1998;Spillantini et al, 1998a). By 9 months of age, these mice recapitulate many pathological changes seen in tauopathies: tangle-like tau inclusions in their brain, neuronal and synaptic loss, atrophy of dendrites, changes in electrophysiological properties of pyramidal neurons, and signs of cognitive and motoric impairments (Ramsden et al, 2005;SantaCruz et al, 2005;Rocher et al, 2010;Crimins et al, 2012;Kopeikina et al, 2013a,b;Scott et al, 2016;Holton et al, 2020;Kubota and Kirino, 2021). In vitro, P301L mutation was shown directly to enhance formation of paired helical filaments and promote β-sheet structure during aggregation (Barghorn et al, 2000;von Bergen et al, 2001;Fischer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%